Efektivitas Program Pemulihan Ekonomi Nasional bagi Pertumbuhan Ekonomi Indonesia - Ulfa Puspa Wanti Widodo; Mutiara Rachma Ardhiani (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effectiveness of the fiscal and monetary policies implemented by the Indonesian government for economic recovery during the pandemic on economic growth. This study uses a quantitative approach and hypothesis testing is carried out using the Autoregressive Integrated Moving Average (ARIMA) method. The sample used is the rate of economic growth in Indonesia from 2010 to 2020. The test results show that the PEN program has a positive impact on consumption levels, FDI, DDI, interest rates, and tax revenues but has not been able to provide a positive stimulus for government spending and GDP. It can be concluded that the implementation of the PEN program has been effective for macroeconomic components in Indonesia but not yet effective enough for increasing GDP as a whole. Keywords: Fiscal Policy, Monetary Policy, Economic Growth, Gross Domestic Product (GDP)